Trace metal concentrations in the abiotic and biotic components of River Rwizi ecosystem in western Uganda, and the risks to human health. Issue 11 (November 2021) - Basooma, Anthony; Teunen, Lies; Semwanga, Nathan; Bervoets, Lieven
Abstract: The distribution of metals in the Rwizi River ecosystem was investigated and human health risks were assessed. Samples of water, sediment, damselfly larvae ( Ceriagrion glabrum ) and fish species ( Brycinus sadleri and Barbus altianalis), were collected at six sites. In all samples the trace elements As, Al, Au, Cd, Co, Cu, Fe, Hg, Mn, Pb, Zn, were quantified. Sediment samples near the gold mine had significantly higher concentrations of Hg, Fe and Al although all the concentrations were below the probable effect concentrations (PEC). The dissolved concentrations of trace metals were within the European standards and WHO drinking water guidelines. However, Fe and Mn concentrations exceeded the standards at three sites. The damselfly larvae were good indicators of local metal pollution. The fish species accumulated metal levels in the order gills > liver > muscle for most metals except for Hg. Multiple regressions between accumulated metals in damselfly with environmental metal levels showed only for Au and Cd significant positive relationships. Relating environmental metal levels and physicochemical characteristics to the levels in the invertebrates, only for Cu and Pb significant relationships were found. With respect to the measured metals, the fish were safe for human consumption in most cases although Brycinus sadleri posed a potential health risk due to a As hazard quotient (HQ) of 2.2 that exceeded the critical value of 1. Similarly, the maximum edible risk-free quantity (Q) for As in Brycinus sadleri was 1.5 g (95 % CI), less than the minimum risk free quantity of 31.5 g. In conclusion, the river water was safe for drinking but the extraction of gold using Hg should be replaced with an environmentally friendly method or an effective wastewater treatment should be instituted. People should be cautioned from consuming Brycinus sadler i to avoid potential health hazards. Graphical abstract: Image 1 Highlights: Surface waters at Katenga and Kayanja were contaminated with gold and mercury. Concerning metals the surface water was generally safe for human consumption at most sites. The sediment trace metal levels posed no ecological risks to the benthic biota. Arsenic and mercury concentrations in Brycinus sadleri muscle posed a potential human health risk. Abstract : Hazard quotient, Trace metals, River Rwizi, Ceriagrion glabrum, Barbus altianalis, Brycinus sadleri .